Pengaruh E-Wom dan Citra Destinasi Terhadap Niat Kunjungan Kembali di Instagram - Absharina, Dheanda; Karmilasari, Karmilasari (Jurnal Ilmiah Pariwisata, 2022)
This study aims to determine the effect of E-WOM and destination image on return visit intentions on Instagram. This research uses quantitative descriptive with multiple regression analysis method of tourist destinations in Bali. Collecting data through a questionnaire using a Likert scale. The number of samples is 120 respondents with purposive sampling technique. The results of the partial study of E-WOM and destination image have a significant effect on return visit intentions on Instagram. E-WOM by using Instagram is very effective and efficient to market tourist destinations in Bali with all good and positive information. The role of a good and high-quality destination image is very large so that visitors want to come back to visit again. The community and local government of the Bali Province are expected to maintain the image of tourist destinations in Bali as well as possible and disseminate it to the internet user community or netizens in order to get positive e-WOM and of course get a positive image that will have a positive impact which is the key to successful remarketing in Bali Province Kywords: E-WOM, Destination Image, Intention of Revisit on Instagram